Teachers’ Training in Designing Mathematics Literacy Questions at SMP and SMK Putra Juang Cianjur - Hutajulu, Masta; Sugandi, Asep Ikin (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
This community service activity aims to enhance the competence of teachers at SMP and SMK Putra Juang in designing mathematics literacy questions aligned with the demands of the Merdeka Curriculum and the national assessment. The training was initiated due to the teachers’ limited understanding of the characteristics of mathematics literacy questions, which emphasisis on critical thinking skills, contextual problem-solving, and conceptual interconnections. The activity was implemented using a participatory approach through workshops, group discussions, and intensive mentoring. The results of the activity indicate an improvement in teachers' ability to develop questions with relevant contexts, diverse representations, and appropriate competency indicators. Furthermore, this activity had a positive impact on teachers’ preparedness for the national assessment and the implementation of literacy-based learning. Based on these findings, this article recommends the continuation of similar training programs as part of efforts to support teachers’ competence development.